2009
DOI: 10.1016/j.matdes.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber length on thermomechanical properties of short carbon fiber reinforced polypropylene composites

Abstract: a b s t r a c tCarbon fiber reinforced composites have all the ideal properties, leading to their rapid development and successful use for many applications over the last decade. In this paper, short carbon fiber reinforced polypropylene (SCF/PP) composite were prepared with melt blending and hot-pressing techniques. The thermomechanical properties of this composite were investigated taking into account the combined effect of mean fiber length. Thermal stability of the composite was studied via the thermal gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
168
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(204 citation statements)
references
References 14 publications
9
168
0
6
Order By: Relevance
“…This result also implied that the stiffness of the biocomposites was considerably improved in comparison to that of the neat PBS. As temperatures further increased to around -50 °C, a dramatic drop in E' could be seen at all curves, which was related to the phase transition of the materials from the rigid glassy state where molecular motions are restricted to a more flexible rubbery state where the molecular chains have greater mobility (Rezaei et al 2009). After that, the E' continued to drop gradually due to the further increased chain mobility of PBS at higher temperature (Kim et al 2005a).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…This result also implied that the stiffness of the biocomposites was considerably improved in comparison to that of the neat PBS. As temperatures further increased to around -50 °C, a dramatic drop in E' could be seen at all curves, which was related to the phase transition of the materials from the rigid glassy state where molecular motions are restricted to a more flexible rubbery state where the molecular chains have greater mobility (Rezaei et al 2009). After that, the E' continued to drop gradually due to the further increased chain mobility of PBS at higher temperature (Kim et al 2005a).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 91%
“…Figure 4 shows the temperature dependence of the loss modulus (E'') for PBS and OPMF/PBS biocomposites of different OPMF weight percentages. The E'' is equivalent to the dissipated energy, and the peak height of loss modulus curves signifies the melt viscosity of a material (Rezaei et al 2009). As can be seen in Fig.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…Long fiber also gives better resistance in crack propagation compared to shorter ones. It was reported in the research of mechanical and thermal properties of short carbon fiber that flexural strength, flexural modulus, and impact strength was increase with the increasing of fiber length [33].…”
Section: Effect Of Different Fiber Length Of Mlf-ldpe Compositesmentioning
confidence: 97%
“…It was obvious that the required energy to pull the shot fiber from the matrix was less that led to dissipation of energy [31] and advancing the crack propagation of the sample thus making the materials to be brittle [27]. Fiber length also affected the properties of MLF reinforced polyethylene where MLF with longer length could withstand a high load and tolerate more stress than shorter ones led to high flexural strength and modulus [33]. Biswas et al [34] reported that the impact strength and flexural strength of coir fiber reinforced epoxy composites increases as the fiber length increases.…”
Section: Effect Of Different Fiber Length Of Mlf-ldpe Compositesmentioning
confidence: 99%
“…5. The loss modulus indicates the material's ability to dissipate energy in the form of heat or molecular rearrangement during the deformation (Rezaei et al 2009). G'' accounts for the viscous component of the complex modulus or the out of phase component with the applied strain, which normally increases with the addition of filler (Singh et al 2010).…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%